Sex gospel in Zimbabwe’s pentecostal christianity as a response to social change: the case of Apostle Kapandura and Mai Lucia Gunguwo - Sipeyiye, Macloud; Mpofu, Phillip (SAGE Publications, 2022)
Sexuality has always been a closely guarded subject in both Christianity and African Traditional Religions (ATRs), and regarded as a sensitive topic unfit for public discussion. In Zimbabwe, there is an emerging trend of sex gospel in Pentecostal Christianity. This has stirred mixed feelings among Christians and ATR adherents. Deploying the religion and social transformation perspective, this netnographic study of Christopher Kapandura of ZAOGA (FIFMI) and Lucia Gunguwo of Eternal Word Ministries’ sermons, explores the eccentric development and argues that sex gospel is inevitable. It is a positive response to social transformation. However, this topical issue grapples with challenges of dissemination methods in the broad public space. The study shows preachers’ creativity and innovation in brand formation in a highly competitive religious market. This is a timely contribution to the meagre scholarship on sex gospel in Pentecostal Christianity, especially its relevance in the context of social change.